Primary care providers' perceptions of physical activity counselling in a clinical setting: a systematic review. Issue 9 (18th June 2012) - Hébert, Emily T; Caughy, Margaret O; Shuval, Kerem
Abstract : Objective: The evidence regarding the effectiveness of promoting physical activity (PA) in primary care is varied. The present study systematically reviews the literature pertaining to primary care providers' perceptions about PA counselling to identify the barriers and enablers to PA counselling in clinical practice. Design: A systematic literature review (through 2011) of quantitative and qualitative studies was conducted. Articles were included in the review if the study population consisted of primary care providers and the study evaluated providers' attitudes and perceptions pertaining to PA counselling. Results: Nineteen articles met the inclusion criteria. Most primary care providers believe PA counselling is important and that they have a role in promoting PA among their patients. However, providers are uncertain about the effectiveness of counselling, feel uncomfortable providing detailed advice about PA, and cite lack of time, training and reimbursement as barriers. Providers are more likely to counsel their patients about PA if they are active themselves, or if they feel their patients' medical condition would benefit from a lifestyle change. Conclusion: Primary care providers are receptive to the notion of PA promotion in the clinical setting, yet numerous individual and organisational barriers need to be addressed to integrate PA counselling into primary care effectively.